Surgery after combination therapy with a tyrosine kinase inhibitor and anti-PD-1 antibody in sarcomatoid hepatocellular carcinoma: case report and literature review - Liang, Bin; Huang, Tao; Kuang, Shao-Lei; Xie, Guang-Yuan; Liu, Tian-Qi; Chen, Yuan-Yuan (Frontiers in Oncology, 2023)
Introduction: Although surgery is the preferred treatment for sarcomatoid hepatocellular carcinoma (SHC), the prognosis remains considerably poor due to early postoperative recurrence and metastasis. Reports on surgery after combined treatment with a tyrosine kinase inhibitor and anti-programmed cell death (PD)-1 antibody are unavailable. Case Presentation:A 69-year-old male patient with SHC was admitted to our hospital for treatment of a liver tumor that was detected on ultrasonography. Abdominal computed tomography with triple-phase enhancement revealed a lesion in the right hepatic lobe that measured 86.0 mm × 75.0 mm × 71.0 mm. Biopsy revealed a pathological diagnosis of liver sarcoma or sarcomatoid carcinoma.The patient subsequently received transcatheter arterial chemo-embolization, as he did not consent to surgery. More than two months later, he received a combination of lenvatinib with camrelizumab, as computed tomography showed an increase in the lesion size (to 123.0 mm × 90.0 mm × 80.0 mm) and lateral growth posterior to the upper pole of the right kidney. Liver resection was performed after 6 months of systemic therapy; pathological examination confirmed a diagnosis of SHC and showed extensive necrosis of tumor cells. Combined treatment with lenvatinib and camrelizumab was continued for 6 months after surgery. The patient has survived for over 24 months after initial diagnosis and is currently tumor-free.Combined systemic therapy with a tyrosine kinase inhibitor and anti-PD-1 antibody may represent a feasible treatment strategy for improving resectability in cases of unresectable SHC. The outcomes with this combination may also be explored in cases of resectable SHC that have a high-risk of recurrence; this may improve the therapeutic effect.